Haplotypes at the Phg-2 Locus Are Determining Pathotype-Specificity of Angular Leaf Spot Resistance in Common Bean - Nay, Michelle M.; Mukankusi, Clare M.; Studer, Bruno; Raatz, Bodo (Frontiers in Plant Science, 2019)
Angular leaf spot (ALS) is one of the most devastating diseases of common bean (Phaseolus vulgaris L.) and causes serious yield losses worldwide. ALS resistance is reportedly pathotype-specific, but little is known about the efficacy of resistance loci against different pathotypes. Here, we report on ALS resistance evaluations of 316 bean lines under greenhouse and field conditions at multiple sites in Colombia and Uganda. Surprisingly, genome-wide association studies revealed only two of the five previously described resistance loci to be significantly associated with ALS resistance. Phg-2 on chromosome 8 was crucial for ALS resistance in all trials, while the resistance locus Phg-4 on chromosome 4 was effective against one particular pathotype. Further dissection of Phg-2 uncovered an unprecedented diversity of functional haplotypes for a resistance locus in common bean. DNA sequence-based clustering identified eleven haplotype groups at Phg-2; One haplotype group conferred broad-spectrum ALS resistance, six showed pathotype-specific effects and the remaining seven did not exhibit clear resistance patterns. Our research highlights the importance of ALS pathotype-specificity for durable resistance management strategies in common bean. Molecular markers co-segregating with resistance loci and haplotypes will increase breeding efficiency for ALS resistance and allow to react faster to future changes in pathogen pressure and composition.